Is there a role for diagnostic scans in the management of intermediate-risk thyroid cancer?. Issue 8 (27th June 2022) - Danilovic, Debora L S; Coura-Filho, George B; Recchia, Giulianna M; Castroneves, Luciana A; Marui, Suemi; Buchpiguel, Carlos A; Hoff, Ana O; Kopp, Peter
Abstract : Radioiodine (RAI) is selectively recommended for intermediate-risk differentiated thyroid carcinomas (DTC). The information gleaned from pretherapy stimulated thyroglobulin levels (sTg) and diagnostic 131 I whole-body scans (DxWBS) to guide therapy remains controversial. The present study aimed at evaluating the impact of preablation sTg and DxWBS in the management of intermediate-risk DTC. A retrospective analysis of 301 intermediate-risk DTC patients submitted to total thyroidectomy and RAI therapy was performed. Pretherapy sTg and DxWBS and post-therapy WBS (RxWBS) findings were analyzed and compared to outcomes. Fifty-two patients (17.3%) had metastases diagnosed by DxWBS and/or RxWBS. The DxWBS identified 10.6% of patients with functioning metastases, including unexpected distant metastases. If combined with SPECT-CT, DxWBS detected RAI-avid metastases more frequently, particularly lymph node metastases (13.1% vs 4.2% planar WBS, P  = 0.015). The DxWBS findings modified patient management in 8.3%. A pretherapy sTg <1 ng/mL was associated with a low false-negative rate for the presence of metastases (5.2%), and its performance in excluding metastasis was improved by a negative DxWBS (2.7% of patients with both negative exams had metastases in RxWBS). A sTg <1 ng/mL predicted statistically significant lower rates of recurrent/persistent disease and biochemical/structural incomplete responses. In conclusion, preablation sTg and DxWBS contribute to the detection of unknown or persistent metastatic disease in intermediate-risk DTC patients. A sTg <1 ng/mL in combination with a negative DxWBS is highly suggestive of the absence of remaining malignant disease, and one may consider deferring RAI ablation if both exams are negative. A stunning effect is rarely observed and it does not impair proper treatment of metastases.